2021
DOI: 10.1186/s12934-021-01527-0
|View full text |Cite
|
Sign up to set email alerts
|

Inducing secondary metabolite production of Aspergillus sydowii through microbial co-culture with Bacillus subtilis

Abstract: Background The co-culture strategy which mimics natural ecology by constructing an artificial microbial community is a useful tool to activate the biosynthetic gene clusters to generate new metabolites. However, the conventional method to study the co-culture is to isolate and purify compounds separated by HPLC, which is inefficient and time-consuming. Furthermore, the overall changes in the metabolite profile cannot be well characterized. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Co-culturing in this case is between different microorganism (fungi and bacteria) in the same medium. Sun et al [ 151 ] carried out co-culture between Aspergillus sydowii and Bacillus subtilis , and found seven new compounds which possess biological activities. Akone et al [ 152 ] reported that, co-culturing of endophytic Chaetomium sp.…”
Section: Enhancement Of Secondary Metabolites Biosynthesis In Fungal ...mentioning
confidence: 99%
“…Co-culturing in this case is between different microorganism (fungi and bacteria) in the same medium. Sun et al [ 151 ] carried out co-culture between Aspergillus sydowii and Bacillus subtilis , and found seven new compounds which possess biological activities. Akone et al [ 152 ] reported that, co-culturing of endophytic Chaetomium sp.…”
Section: Enhancement Of Secondary Metabolites Biosynthesis In Fungal ...mentioning
confidence: 99%
“…To investigate the main components in the TFM, the data of high-performance liquid chromatography (HPLC) and high-resolution LC–MS/MS were imported into MS-DIAL and MS-FINDER software, an assay integrating the computational programs. The software combination provided higher prediction accuracy than the traditional LC–MS/MS analysis, which has been validated in our previously study . A total of 30 compositions were identified and are listed in Table .…”
Section: Resultsmentioning
confidence: 81%
“…160 Co-culture of A. sydowii wth the bacterium Bacillus subtilis induced production of 25 known and new metabolites by the fungus including serine sydonate 345 and an isomer of macrolactin U 346. 161 Furanaspermeroterpenes A 347 and B 348, meroterpenoids with an unique 6/6/ 6/5/5 pentacyclic skeleton were isolated from a gastropodderived Aspergillus terreus strain, along with ve further meroterpenes 349-353. 162 An OSMAC approach was utilised in the isolation of phenolic derivatives 354 and 355 from two separate Aspergillus strains and a known synthetic derivative 356 was obtained as a new MNP from the latter strain also.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…160 Co-culture of A. sydowii wth the bacterium Bacillus subtilis induced production of 25 known and new metabolites by the fungus including serine sydonate 345 and an isomer of macrolactin U 346 . 161 Furanaspermeroterpenes A 347 and B 348 , meroterpenoids with an unique 6/6/6/5/5 pentacyclic skeleton were isolated from a gastropod-derived Aspergillus terreus strain, along with five further meroterpenes 349–353 . 162…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%